2008
DOI: 10.1536/ihj.49.281
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Effect of Bisoprolol, a Highly Selective .BETA.1-Blocker, in Patients With Paroxysmal Atrial Fibrillation

Abstract: SUMMARYIn the treatment of arrhythmia, β-blockers are mainly used to regulate the heart rate. However, β-blockers are also known as drugs with an antiarrhythmic effect due to the suppression of sympathetic activity. We evaluated the antiarrhythmic effects of a highly selective β 1 -blocker, bisoprolol, in patients with diurnal paroxysmal atrial fibrillation (P-AF).A total of 136 patients with symptomatic diurnal P-AF were enrolled. Patients were divided into a diurnal-specific P-AF group and a diurnal & noctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Ishiguro et al reported that bisoprolol has a defibrillation effect that causes AF to convert to sinus rhythm in paroxysmal AF patients because of reduction in HR. 27 In our study, reduction of HR was more prominent in the bisoprolol group than that in the carvedilol group at 18 months. Higher percentage of normal sinus rhythm in the bisoprolol group at 18 months could attribute to the lower HR in this group, because HR in AF patients reduces after defibrillation.…”
Section: Konishi M Et Alsupporting
confidence: 43%
See 1 more Smart Citation
“…Ishiguro et al reported that bisoprolol has a defibrillation effect that causes AF to convert to sinus rhythm in paroxysmal AF patients because of reduction in HR. 27 In our study, reduction of HR was more prominent in the bisoprolol group than that in the carvedilol group at 18 months. Higher percentage of normal sinus rhythm in the bisoprolol group at 18 months could attribute to the lower HR in this group, because HR in AF patients reduces after defibrillation.…”
Section: Konishi M Et Alsupporting
confidence: 43%
“…Several trials performed on Japanese patients with HF have shown that the BP and HR decrease adequately by administering low dosages of carvedilol and bisoprolol. 8, 27 Tamura et al also reported that low dosages of cavedilol significantly improve LVEF and BNP levels in HF patients after 6 months of treatment. 28 These differences in the dosages used between Japanese patients and other nationalities can be illustrated by the pharmacological heterogeneity of β-blockers.…”
Section: Konishi M Et Almentioning
confidence: 96%
“…[1][2][3][4][5] This is also emphasized in patients after successful cardioversion of AF. While ACE inhibitors and angiotensin receptor blockers are evidently effective to a certain extent, the beneficial effects of statins on AF prevention are still controversial.…”
mentioning
confidence: 99%
“…Bisoprolol has an antiarrhythmic eff ect against sympathetic diurnal paroxysmal atrial fi brillation. It also signifi cantly reduces morbidity and mortality in stable chronic heart failure patients (Ishiguro et al, 2008;De Groote et al, 2007;Metra et al, 2007). Several previous reports have described the determination of bisoprolol in plasma using analytical methods including HPLC-FL (Taguchi et al, 2005;Braza et al, 2002;Eastwood et al, 1990;Horikiri et al, 1998), HPLC-DAD (Caudron et al, 2004), GC-MS (Shangguan et al, 2008) and LC-MS/MS Ding et al, 2007;Jovanovic et al, 2006;Bhatt et al, 2007;Kristoff ersen et al, 2007;Maurer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%